Efeito do manejo hídrico durante a rustificação em mudas de Gallesia integrifolia (Spreng.) Harms e Handroanthus impetiginosus (Mart. ex DC.) Mattos - Lima, Paulo Ricardo (2014)
The knowledge of Morphophysiological mechanisms that allow a plant tolerate water stress conditions constitutes important tool for analyzing the quality of seedlings, so it the work aimed to quantify the effects of water management in the period of rustification in seedlings of Handroanthus impetiginosus (Mart. ex DC.) Mattos and Gallesia integrifolia (Spreng.) Harms by means of foliar thermometry and parameters morphometric of quality and additionally analyze the performance of seedlings after the rustification, in soil sandy and loamy soil. The experiment was conducted in a protected ambient at the State University of West Paraná, campus Marechal Cândido Rondon - PR. The treatments were comprised of four hydric regimes: daily irrigation (control), every two, three and four days in 60 seedlings per treatment for four weeks. The mensurations involved the measurement of the leaf temperature (TF), the increments in height, the stem diameter, in the mass dry of root , in the mass dry of shoot and leaf area. The mensurations of TF occurred at the end of each irrigation management cycle and for the other variables were held measurements at the beginning and end of rustification. After the impositions of hydric managements, the seedlings were taken to pots containing sandy soil and clay soil to check the influence of different hydric management as well as soil type in the seedling survival. The analysis between the control treatment and irrigation every two days resulted in significant differences (P> 0,05) merely for leaf area, whereas in and both species studied presented decreased of leaf area with the increase of hydric restriction. Seedlings of H. impetiginosus with of irrigation cycles every three days, showed a reduction in the rate of growth in diameter of 29%, of 58% to increment the dry mass of shoots and 32% for leaf area compared to the management control. Seedlings of G. integrifolia irrigated every three days showed no significant differences (P> 0,05) compared with irrigated daily. The irrigation management every four days in seedlings of H. impetiginosus enabled higher speed of growth of the root system and reduced aerial growth, resulting in warming the leaf, whereas the irrigation management every four days in seedlings of G. integrifolia presented reduction in the rate of growth of the shoot and not presented difference (P> 0,05) in the root system growth and also resulted in leaf warming. The use of the infrared thermometry allows benchmarking the leaf temperature during rustification of seedlings of H. impetiginosus and G. integrifolia. Was no influence of soils in the seedling survival of H. impetiginosus and G. integrifolia, and symptoms of hydric deficit always if manifested first in clay soil, mainly in seedlings not adapted to hydric stress. In both species, the symptoms of hydric deficit presented by the seedlings of different management hydrics showed that seedlings submitted to the irrigation regimes every three and four days, were attenuating slowly the symptoms of hydric deficit compared with others hydrics management